Application of Think Pair Share Method to Improving Motivation and Mathematics Learning Outcomes of Class VIII Students - Martina Rada; Erawati Ni Ketut; Eka Indrawan I Putu (Emasains : Jurnal Edukasi Matematika dan Sains, 2021)
This study aims to improve motivation and learning outcomes of mathematics in students in Class VIII A of Denpasar National Junior High School through the application of the Think Pair Share (TPS) method. The type of research used is classroom action research (CAR) because the problems solved come from classroom learning practices. This research was conducted in two cycles, each cycle consisting of four stages, namely: planning, acting, observing ( observing) and reflection (reflection). The subjects of this study were students of class VIII A of Denpasar National Junior High School, which amounted to 28 people. Techniques in data collection include: tests, questionnaires, interviews, and documentation. The research instruments are motivation questionnaires and learning outcomes tests. The results showed that the application of the Think Pair Share method can increase motivation and learning outcomes. In the first cycle the highest score was 90 and the lowest score was 30, in the second cycle the highest score was 90 and the lowest was 50. The average student learning motivation in the first cycle was 60 in the second cycle70.